Sakkadas, Savvas - (:unkn) unknown (My University, 2026)
Savvas Sakkadas is Assistant Professor in the Department of Hotel and Tourism Management. He has MA in International Relations from Indianapolis University (USA) and (MBA) in International Business from Fairleigh Dickinson University as well as a (B.Sc) degree in Hotel & Catering Management from the same University. He is also a licensed Cyprus Tourism Organization, Tourist Guide. He studied in the field of Developing Tourism in Small State Islands at Tesamek Polytechnic in Singapore. He has eighteen years of teaching experience at the undergraduate level in the fields of hospitality and tourism in private and public tertiary education in Cyprus. He served as College Coordinator for Travel and Tourism Studies at Intercollege, and as the Head of the Hospitality Studies at the Higher Hotel Institute, Cyprus. His research activities focus on Cultural Heritage Tourism, Interpretation of Heritage Sites, and Visitors’ Authentic experience.